2019
DOI: 10.1007/s11145-019-09966-3
|View full text |Cite
|
Sign up to set email alerts
|

The relations between children's comprehension monitoring and their reading comprehension and vocabulary knowledge: an eye-movement study

Abstract: Poor reading comprehension may be due to having ineffective comprehension monitoring, the metacognitive process of evaluating and regulating comprehension. When comprehension breaks down due to an inconsistency either at the word-level (e.g., due to an unfamiliar word) or at the sentence-level (e.g., due to contradictory information), readers may identify the misunderstanding and take steps to regulate their comprehension. In the current study, we utilized two eye-movement tasks (one newly developed) to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
1
29
0
5
Order By: Relevance
“…Furthermore, children with stronger academic language skills (including picture vocabulary, story retelling and academic knowledge) showed more rereading of inconsistent continuations but less rereading of consistent continuations. Zargar, Adams, and Connor (2020) found that children who scored higher on a standard reading comprehension test also engaged in more rereading of inconsistent continuations. Finally, in their study with 9-to 10-year-olds, Hessel et al (2021) observed increased go-past times, rereading times, and total reading times for the critical region for inconsistent versus consistent continuations, as well as more regressions into the critical region and longer rereading times.…”
Section: Np/z Ambiguitymentioning
confidence: 94%
“…Furthermore, children with stronger academic language skills (including picture vocabulary, story retelling and academic knowledge) showed more rereading of inconsistent continuations but less rereading of consistent continuations. Zargar, Adams, and Connor (2020) found that children who scored higher on a standard reading comprehension test also engaged in more rereading of inconsistent continuations. Finally, in their study with 9-to 10-year-olds, Hessel et al (2021) observed increased go-past times, rereading times, and total reading times for the critical region for inconsistent versus consistent continuations, as well as more regressions into the critical region and longer rereading times.…”
Section: Np/z Ambiguitymentioning
confidence: 94%
“…In the situation model construction process, cognitive skills, such as comprehension monitoring and inference making, are necessary to detect internal and external inconsistences and draw inferences ( Cain et al, 2004 ; Connor et al, 2015 ; Oakhill et al, 2015 ; Wong et al, 2017 ). As such, language skills might not only have direct effect on reading by allowing readers to build initial propositions but also indirect effect on reading by facilitating readers’ engagement in comprehension monitoring, which is a higher level cognitive skill built on foundational language skills ( Kintsch, 1988 ; Perfetti et al, 2007 ; Zargar et al, 2020 ). That is, the language and cognitive skills that underlie the three sub-processes of reading might have hierarchical and dynamic relations among them ( Cromley and Azevedo, 2007 ; Kim, 2015 , 2016 , 2017 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, vocabulary knowledge is found to be a powerful predictor for comprehension monitoring ( Cain et al, 2004 ; Perfetti et al, 2007 ). Meaning of related words, such as synonyms, antonyms, and category exemplars, in the text provides clues for internal consistency or inconsistency ( Zargar et al, 2020 ). A rich semantic network of words associated with the topic makes it easier for readers to detect inconsistency between propositions built from the text and world knowledge ( Currie and Cain, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Connor (2016) further highlighted that proficient readers are more likely to monitor their real-time comprehension by rereading and self-questioning and are more likely to use appropriate reading strategies such as rereading or using context clues to repair their misunderstanding and facilitate their comprehension when they are confronted with an unfamiliar word (Cain et al, 2004). This has been also suggested by previous eye-movement studies demonstrating longer rereading times for unfamiliar or implausible words, especially for better comprehenders (Zargar et al, 2020).…”
Section: Using Reading and Vocabulary Theories To Identify User Log Variablesmentioning
confidence: 56%